Assessment of goals and priorities in patients with a chronic condition: a secondary quantitative analysis of determinants across 11 countries - Neeltje P. C. A. Vermunt; Gert P. Westert; Marcel G. M. Olde Rikkert; Marjan J. Faber (Taylor & Francis Group, 2018)
Objective: To assess the impact of patient characteristics, patient-professional engagement, communication and context on the probability that healthcare professionals will discuss goals or priorities with older patients. Design: Secondary analysis of cross-sectional data from the 2014 Commonwealth Fund International Health Policy Survey of Older Adults. Setting: 11 western countries. Subjects: Community-dwelling adults, aged 55 or older. Main outcome measure: Assessment of goals and priorities. Results: The final sample size consisted of 17,222 respondents, 54% of whom reported an assessment of their goals and priorities (AGP) by healthcare professionals. In logistic regression model 1, which was used to analyse the entire population, the determinants found to have moderate to large effects on the likelihood of AGP were information exchange on stress, diet or exercise, or both. Country (living in Sweden) and continuity of care (no regular professional or organisation) had moderate to large negative effects on the likelihood of AGP. In model 2, which focussed on respondents who experienced continuity of care, country and information exchange on stress and lifestyle were the main determinants of AGP, with comparable odds ratios to model 1. Furthermore, a professional asking questions also increased the likelihood of AGP. Conclusions: Continuity of care and information exchange is associated with a higher probability of AGP, while people living in Sweden are less likely to experience these assessments. Further study is required to determine whether increasing information exchange and professionals asking more questions may improve goal setting with older patients.Key points   A patient goal-oriented approach can be beneficial for older patients with chronic conditions or multimorbidity; however, discussing goals with these patients is not a common practice.The likelihood of discussing goals varies by country, occurring most commonly in the USA, and least often in Sweden. Country-level differences in continuity of care and questions asked by a regularly visited professional affect the goal discussion probability. Patient characteristics, including age, have less impact than expected on the likelihood of sharing goals.